The effectiveness of Chuna manual therapy based on radiographic malposition diagnosis in patients with non-acute low back pain: A study protocol for a randomized, assessor-blind, parallel-group, controlled trial - Jungho Jo; Yeong Ha Jeong; Tae-Yong Park; Young Cheol Na; Jun-Su Jang; Minho Choi; Junghan Lee; Kang-san Kim; Yoonhee Kim; Seungkwan Choi; Wonbae Ha; Jin-Hyun Lee (PLoS ONE, 2026)
Background Chuna manual therapy is a Korean therapeutic modality that is widely used for treating low back pain. First, spinal alignment is radiographically assessed, followed by treatment delivery as per the assessment. There is emerging evidence supporting radiograph-based diagnostic methods in Chuna manual therapy. However, there remains limited high-quality clinical evidence regarding the effectiveness of treatment tailored to specific diagnostic types. Accordingly, this study aims to evaluate the effectiveness and safety of Chuna manual therapy in patients with non-acute low back pain radiographically diagnosed with spinal malposition. Methods This two-arm, parallel-group, assessor-blind, randomized controlled trial will include 46 participants with non-acute low back pain lasting ≥3 weeks and an average Numeric Rating Scale (NRS) score ≥4 from two hospitals. Participants will be randomly assigned in a 1:1 ratio to the usual care plus Chuna manual therapy intervention group (n = 23) or the usual care intervention group (n = 23). Participants in the intervention group will receive individualized Chuna manual therapy based on the radiographic diagnosis twice per week for 4 weeks. The primary outcome will be the change in the NRS score for low back pain at Week 4 and Week 12 compared with baseline. The secondary outcomes will include changes in the Oswestry Disability Index, Roland Morris Disability Questionnaire, EuroQol-5 Dimension, radiographic alignment indices, Range of Motion assessment, and safety evaluation. Discussion This will be the first randomized controlled trial to investigate the effectiveness of Chuna manual therapy based on the radiographic diagnosis of spinal malposition in patients with non-acute low back pain. The findings may strengthen the evidence base for diagnostic and therapeutic processes in Chuna manual therapy. Trial registration This study is registered with the Clinical Research Information Service of the Korea Disease Control and Prevention Agency. Registration number: KCT0011042.